KONTRIBUSI KEPEMIMPINAN TRANSAKSIONAL KEPALA SEKOLAH DAN MOTIVASI BERPRESTASI GURU TERHADAP PROFESIONALITAS GURU SMA PADANG UTARA - Areva, Desi (Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
This study is motivated by the phenomenon of the decline of professionalism of North Padang high school teacher. This study aims to determine the contribution of transactional leadership principals and achievement motivation of teachers on high school teachers professionalism in the district of North Padang. This study classified to quantitative study. The population in this study are all high school teachers in North Padang, amounting to 202 people. Of the entire population sample of 135 people was set in stratified proportional random sampling. Data collection instrument was a questionnaire. The collected data were analyzed using statistical analysis with SPSS version 17.00. The results showed that: (1) Transactional leadership principals contributed significantly on the professionalism of a high school teacher in North Padang at 46.60%; (2) Achievement motivation contributed significantly on the professionalism of a high school teacher in North Padang at 38.30%, and (3) Transactional leadership and achievement motivation principals together contributed significantly towards high school teacher professionalism in Padang Utara by 58%. Keywords: Transactional leadership, need for achievement, teacher professionalism